Airport Aura. A Spatial History of Airport Infrastructure. - Mironov, Lilia (vdf Hochschulverl., 2020)
Throughout the 20th century and into the 21st, the emergence of airports as gateways for their cities has turned into one of the most important architectural undertakings. Ever since the first manned flight by the Brothers Orville and Wilbur Wright on December 17th 1903, utilitarian sheds next to landing strips on cow pastures evolved into a completely new building type over the next few decades – into places of Modernism as envisioned by Le Corbusier and Frank Lloyd Wright (who themselves never built an airport), to eventually turn into icons of cultural identity, progress and prosperity. Many of these airports have become architectural branding devices of their respective cities, regions and countries, created by some of the most notable contemporary architects. This interdisciplinary cultural study deals with the historical formation and transformation of the architectural typology of airports under the aspect of spatial theories. This includes the shift from early spaces of transportation such as train stations, the synesthetic effect of travel and mobility and the effects of material innovations on the development, occupation and use of such spaces. The changing uses from mere utilitarian transportation spaces to ones centered on the spectacular culture of late capitalism, consumption and identity formation in a rapidly changing global culture are analyzed with examples both from architectural and philosophical points of view. The future of airport architecture and design very much looks like the original idea of the Crystal Palace and Parisian Arcades: to provide a stage for consumption, social theatre and art exhibition.
Keywords: Verkehrsbauwerk; Flughafen; Flughafenterminal; Architektursymbol; Architekturkonzept; Flughafenbahnhof; Verkehrsanbindung; Beispielsammlung; International; Standortfaktor; Baugeschichte; Nutzungskonzept; Attraktivitätsfaktor; Unterhaltung; Erlebniswelt; Aerotropolis; Branding; Flughafentypologie